2010
DOI: 10.2217/whe.10.40
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity, Obesity and Eating Habits Can Influence Assisted Reproduction Outcomes

Abstract: Eating habits, physical activity and obesity could affect clinical outcomes of assisted reproduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
3
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 44 publications
0
15
3
4
Order By: Relevance
“…Department of Health and Human Services [USDHHS], 2008). Exercise promotes the viability of a pregnancy, improves fertility rates and perinatal outcomes, and reduces miscarriage rates in obese women with a history of reproductive complications (Clark et al, 1998; Ferreira et al, 2010). Active pregnant women also report lower depressive/anxiety symptoms than sedentary pregnant women (Da Costa et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Department of Health and Human Services [USDHHS], 2008). Exercise promotes the viability of a pregnancy, improves fertility rates and perinatal outcomes, and reduces miscarriage rates in obese women with a history of reproductive complications (Clark et al, 1998; Ferreira et al, 2010). Active pregnant women also report lower depressive/anxiety symptoms than sedentary pregnant women (Da Costa et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Dietas de baixo índice glicêmico melhoram a sensibilidade à insulina de diabéticos e diminuem os níveis de HbA1c, enquanto que a excessiva ingestão de carboidrato pode levar a um aumento na IGF-I nos níveis de androgênios e de SHBG, resultando numa condição semelhante a encontrada na SOP (Chavarro et al, 2009), fato que poderia estar relacionado com a maior dificuldade para ovulação das mulheres e sucesso da reprodução assistida. Outro estudo que relacionou alimentação com resultados de FIV/ICSI sugere que a taxa de fertilização foi maior nas pacientes que consumiam mais vegetais e pães integrais, enquanto que a ingestão de refrigerante, chocolate e o tabagismo foram maiores nos ciclos que não resultaram em gestação (Ferreira et al, 2010). Chavarro et al (2009) identificaram o consumo de 2 ou mais refrigerantes por dia (com açúcar ou diet) como fator de risco para infertilidade de causa ovulatória, independente de seu conteúdo de cafeína.…”
Section: Resultsunclassified
“…O estado nutricional reflete a saúde reprodutiva desde os primeiros estágios: o baixo peso causa desequilíbrio hormonal, afeta negativamente a ovulação e menstruação e desafia o início da gestação. Por outro lado, o excesso de gordura corporal afeta a ovulação devido à sensibilidade à insulina, excesso de androgênios e leptina (Cetin et al, 2010) Ferreira et al (2010 identificaram que a obesidade prejudica a qualidade oocitária e os resultados dos ciclos de ICSI. Dados de 436 pacientes sugerem que as mulheres obesas bebem mais refrigerantes e praticam menos exercício físico do que as mulheres eutróficas.…”
Section: Análise Estatísticaunclassified
“…Other studies support the findings of an association between infertility and history of depressive disorder as well as associations between smoking and infertility and difficulty staying pregnant. 1420 Additional female risk factors for infertility and difficulty staying pregnant reported in other studies that were not explored or not found to be associated with infertility with the BRFSS data include abnormal menstrual cycle patterns and menstrual cycle length, 21,22 obesity, 18,2329 intense physical activity, 28,29 lower folate intake, 30 alcohol consumption, 1719,28,31 diabetes, 23 cancer, 3234 karyotypic disorders, 17 immunological rejection, 23 thrombophilias, 17,23 endocrinological issues, 17,35,36 infections, 18,23 environmental pollutants, 18 and delivery history. 19 …”
Section: Discussionmentioning
confidence: 97%